Physicomechanical and thermal analysis of bulk-fill and conventional composites - Armiliana Soares NASCIMENTO; José Filipe Bacalhau RODRIGUES; Rodolfo Henrique Nogueira TORRES; Kleilton Oliveira SANTOS; Marcus Vinicius Lia FOOK; Monica Soares de ALBUQUERQUE; Eliane Alves de LIMA; Pedro Tardelly Diniz FILGUEIRA; João Batista Morais dos SANTOS; Leonardo Jose Rodrigues de OLIVEIRA; Rodivan BRAZ (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract The aim of this study was to evaluate the degree of conversion (DC) and the thermal stability of bulk-fill and conventional composite resins. Eleven composite resin samples were prepared to evaluate the DC, Vickers microhardness (VMH), mass and residue/particle loss, glass transition temperature (Tg), enthalpy, and linear coefficient of thermal expansion (CTE) using infrared spectroscopy (FTIR), microdurometer analyses, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and dilatometry (DIL). The data were subjected to statistical analysis, with a significance level of 95%. DC and VMH were not influenced by the polymerized side of the sample, and statistical differences were recorded only among the materials. Decomposition temperature, melting, and mass and residue loss were dependent on the material and on the evaluation condition (polymerized and non-polymerized). Tg values were similar between the composites, without statistically significant difference, and CTE ranged from 10.5 to 37.1 (10-6/°C), with no statistical difference between the materials. There was a moderate negative correlation between CTE and the % of load particles, by weight. Most resins had a DC above that which is reported in the literature. TGA, Tg, and CTE analyses showed the thermal behavior of the evaluated composites, providing data for future research, assisting with the choice of material for direct or semidirect restorations, and helping choose the appropriate temperature for increasing the DC of such materials.